2020
DOI: 10.1038/s41598-020-66702-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of high fat diet-induced obesity on oocyte mitochondrial functions in inbred and outbred mice

Abstract: Maternal obesity can cause reduced oocyte quality and subfertility. Mitochondrial dysfunction plays a central role here, and most often inbred mouse models are used to study these pathways. We hypothesized that the mouse genetic background can influence the impact of high fat diet (HFD)-induced obesity on oocyte quality. We compared the inbred C57BL/6 (B6) and the outbred Swiss strains after feeding a HFD for 13w. HFD-mice had increased body weight gain, hypercholesterolemia, and increased oocyte lipid droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 51 publications
9
52
0
Order By: Relevance
“…Indeed, LD accumulation, composition, and localization are dynamic during oocyte maturation [4, 12], LDs are hubs for FA trafficking, and FA levels (including that of AA) are critical for oocyte development in many species [7, 13, 105]. Further, in both mouse models and human patients, metabolic syndrome causes LD clustering in oocytes, failures in oocyte maturation, and decreased fertility [1315, 106, 107]. But does this relate to PG signaling?…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, LD accumulation, composition, and localization are dynamic during oocyte maturation [4, 12], LDs are hubs for FA trafficking, and FA levels (including that of AA) are critical for oocyte development in many species [7, 13, 105]. Further, in both mouse models and human patients, metabolic syndrome causes LD clustering in oocytes, failures in oocyte maturation, and decreased fertility [1315, 106, 107]. But does this relate to PG signaling?…”
Section: Discussionmentioning
confidence: 99%
“…The pathways for ROS production and oxidative stress have been reported to be upregulated in the liver of mice consuming an HFD, and this event precedes the onset of insulin resistance [12]. Moreover, both animal and human studies have reported that longterm HFD feeding leads to increased oxidative stress and dysfunctional mitochondria in many organs [13][14][15][16] and induces ER stress in vitro [6][7][8][9]. The functional crosstalk between oxidative stress and ER stress is well described.…”
Section: Introductionmentioning
confidence: 99%
“…Oocytes, collected from obese patients but also from Western Type diet induced obese mice, displayed an impaired quality, indicated by high rates of meiotic spindle abnormalities, increased mitochondrial ultrastructural abnormalities, altered mitochondrial membrane potential and increased cellular oxidative stress levels [ 16 19 ]. Furthermore, mitochondrial DNA (mtDNA) copy number and mitochondrial biogenesis in oocytes from obese mice were altered [ 18 ] and higher levels of lipid accumulation and abnormal lipid distribution in oocytes were present [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%